2012
DOI: 10.1016/j.annemergmed.2011.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Access During Out-of-Hospital Emergency Care of Noninjured Patients: A Population-Based Outcome Study

Abstract: Study objective Advanced, pre-hospital procedures such as intravenous access are commonly performed by emergency medical services (EMS) personnel, yet little evidence supports their use among non-injured patients. We evaluated the association between pre-hospital, intravenous access and mortality among non-injured, non-arrest patients. Methods We analyzed a population-based cohort of adult (aged ≥18 years) non-injured, non-arrest patients transported by four advanced life support agencies to one of 16 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…We linked encounters to the Washington State Death records. Further details on this cohort and success of record linkage success are previously described . In brief, we used probabilistic matching to deduplicate and link EMS records with manual validation, followed by hierarchical deterministic matching of EMS to hospital and death records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We linked encounters to the Washington State Death records. Further details on this cohort and success of record linkage success are previously described . In brief, we used probabilistic matching to deduplicate and link EMS records with manual validation, followed by hierarchical deterministic matching of EMS to hospital and death records.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated Z‐statistics as the beta estimate divided by the standard error of the beta, derived from multivariate models that included age, sex, prehospital vital signs (respiratory rate, SaO 2 , Glasgow Coma Scale score, heart rate), transport mode, primary diagnosis category, and paramedic care (yes/no) and fixed effects for responding fire unit, receiving hospital, and year in cohort. These variables were selected a priori as known confounders from our prior work, and parameterized as described in “additional variables.” We did not categorize any ordinal or continuous variables other than prehospital sBP. We included responding fire units and receiving hospitals as fixed effects in the model to account for the nonindependence of observations.…”
Section: Methodsmentioning
confidence: 99%
“…Although certain prehospital interventions such as intravenous catheter insertion are associated with a reduction in mortality, others have found that specific populations such as trauma patients are 2.63 times more likely to die for every procedure completed in the prehospital setting. 6,7 Given the conflicting data regarding the impact prehospital procedures have on patient outcomes we need to have a better understanding of national EMS patterns of procedures. Focusing the scope of practice and procedure training opportunities for prehospital responders may be further refined with a better knowledge of how often particular procedures are performed.…”
Section: Introductionmentioning
confidence: 99%
“…These patients often require immediate interventions such as defibrillation or intravenous (IV) therapy. According to Seymour et al, [1] obtaining IV access is a commonly performed prehospital procedure. However, it can potentially have a wide range of complications, including thromboembolism and sepsis.…”
mentioning
confidence: 99%